(untitled) (Bangladesh Rice Journal, 2023)
This study evaluated the profitability dynamics of blast affected Boro rice cultivation within specific regions of Kushtia District of Bangladesh during the period of 2018-19. A total of 90 farmers, with 30 from each upazila, were selected randomly for participation in this study. The findings revealed substantial yield losses, with the most significant impact observed among11% farmers affected by a disease severity scale of 9 in BRRI dhan28, resulting in a yield loss of 3.92 t/ha. Similarly, a blast severity scale of 9 led to yield losses of 2.0 t/ha in BRRI dhan29, affecting 7% of farmers. The Miniket cultivar exhibited a yield loss of 1.70 t/ha among 56% of farmers with a severity scale of 5. Interestingly, Mirpur experienced devastating losses for both BRRI dhan28 and BRRI dhan29, while Kushtia Sadar suffered significant yield losses for the Miniket cultivar based on disease severity and yield impact. Application of Nativo 75 WG (0.40 Kg/ha) and Trooper 75 WP (0.50 Kg/ha) at the lowest (3%) disease incidence resulted in a remarkable 68.97% increase in yield for BRRI dhan29 in Bheramara. Conversely, spraying of Amistar Top 325 SC (0.56 l/ha) did not lead to increase yield. In Miniket cultivar at Bheramara, Nativo 75 WG (0.45 Kg/ha) and Amistar Top 325 SC (0.37 l/ha) resulted in a lower yield of 2.99 t/ha due to application at a higher (50%) disease incidence. Furthermore, a yield increase of 69.67% was observed with the application of Nativo 75 WG (0.34 kg/ha) in the Miniket cultivar at Kushtia Sadar. The highest gross return, gross margin, net return, and benefit-cost ratio were recorded in Bheramara, amounting to Tk 1,24,084/ha, Tk 46,037/ha, Tk 5,797/ha, and 1.05, respectively. Notably, BRRI dhan29 exhibited the maximum gross return and yield of Tk 1,32,435/ha and 6.14 t/ha, respectively, whereas BRRI dhan28 demonstrated the lowest gross return and net return of Tk 1,09,737/ha and (-) Tk 8,321/ha, respectively, due to higher blast disease incidence. Labor costs constituted the largest share (34.10%) of the total rice production expenses. Despite BRRI dhan28 exhibiting lower net and gross returns per hectare due to higher blast disease incidence, the highest yields in BRRI dhan29 were attributed to its comparatively lower disease infection rate among the three varieties. Evidently, the cultivation of the Miniket cultivar resulted in higher net returns due to its superior market price and quality, especially when disease incidence was lower compared to BRRI dhan28. This emphasizes the importance of blast management strategies and the use of resistant varieties with high yield potential and market value in ensuring sustainable productivity and profitability in Boro rice production. Bangladesh Rice J. 26 (2): 1-18, 2022